Strategic Orientation and Customer Relationship Management:: A Contingency Framework of CRM Success - Shannahan, Kirby; Shannahan, Rachelle; Alexandrov, Aliosha (Journal of Comparative International Management)

(untitled) (None, 2010)
Since their inception, the failure rate of customer relationship management (CRM) projects continues to be high. Using the "Miles and Snow" (1978) strategic typology, this paper advances a contingency framework to explain the failure rates and to better predict the success of CRM projects. The strategic typology perspective allows for the integration of firm strategic orientation, environmental factors, and customer characteristics for the development of a broad framework for understanding CRM success and failure. Several propositions are advanced for how internal and external factors can affect the success of CRM initiatives.